Универсальная система авиационного мониторинга, осуществляемого путем оптического дистанционного зондирования земной поверхности, как средство повышения оперативности реагирования на чрезвычайные ситуации - Sizikov, Алексей; Prudnikov, Сергей; Khvaley, С. (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2013)
The article provides the sequences of actions emergency situation detection using the existing domestic samples of aviation monitoring system of different nature emergency situations and a universal system of aviation monitoring which is independent of the operator. The advantages of the last one to enhance the effectiveness of emergency response in this article are substantiated.